The Influence of Stress and Strain on the Tempering of SAE 4340 Martensitic Steel - Rochim Suratman (Institute for Research and Community Services (LPPM) ITB, 1982)
Abstract. An investigation into the influence of stress and/or strain on the tempering of SAE 4340 martensitic steel is being done. The as-quenched steel is tempered at several temperatures (100° - 600°C) with and without the influence of stress. The resulting changes in hardness and structure were then followed by microhardness measurements and electron microscopy. The primary variables of interest in this work are hardening conditions, tempering time, tempering temperature, stress, and strain during tempering. From the experimental result it appears that the hardness of steel SAE 4340 tempered under stress between 100°C and 300°C is higher than the hardness of the same steel tempered without stress, while the hardness of steel tempered under stress al a temperature higher than 300°C is lower than the hardness of steel tempered without stress. In all cases, at higher stresses the specimens undergo plastic deformation during tempering and it is seen that the plastic strain has more influence on the tempering than the stress. The electron microscopic observations show that the increase in hardness, due to the strain occuring during tempering, is caused mainly by a more abundant precipitation of carbides of about the same shape and size as in specimens tempered without stress. When the strain occuring during tempering causes a lower hardness, the carbide precipitations are coarser, more equlaxed and fewer than after tempering without stress. In all cases, at higher stresses the specimens undergo plastic deformation during tempering and it is seen that the plastic strain has more influence on the tempering than the stress. The electron microscopic observations show that the increase in hardness, due to the strain occurring during tempering, is caused mainly by a more abundant precipitation of carbides of about the same shape and size as in specimens tempered without stress. When the strain occurring during tempering causes a lower hardness, the carbide precipitations are coarser, more equiaxed and fewer than after tempering without stress. Pengaruh Tegangan dan/atau Regangan yang Diberikan pasa saat Menemper Baja Martensit SAE 4340Sari. Suatu penyelidikan mengenai pengaruh tegangan dan/atau regangan yang diberikan selama menemper baja martensit SAE 4340 terhadap proses penguraian martensit dan proses presipitasi. Hasil-hasil percobaan menunjukkan bahwa kekerasan baja SAE 4340, setelah distemper pada suhu antara 100°C dan 300°C di bawah pengaruh tegangan, lebih keras dibandingkan dengan kekerasannya setelah distemper tanpa pengaruh tegangan. Setelah distemper di bawah pengaruh tegangan pada suhu yang lebih tinggi dari 300°C, kekerasan dari semua baja yang diamati menjadi lebih rendah dibandingkan dengan kekerasannya setelah distemper tanpa pengaruh tegangan. Dari hasil pengamatan dengan bantuan mikroskopelektron, ternyata bahwa penyebab dari bertambah kerasnya kekerasan baja setelah ditemper di bawah pengaruh tegangan, adalah adanya presipitat-presipitat yang jauh lebih banyak jumlahnya dibandingkan dengan jumlah presipitat-presipitat yang ada setelah ditemper tanpa pengaruh tegangan; sedangkan penyebab dari berkurangnya kekerasan baja setelah ditemper di bawah pengaruh tegangan adalah adanya presipitat-presipitat yang kasar dan lebih sedikit jumlahnya dibandingkan dengan presipitat-presipitat setelah ditemper tanpa pengaruh tegangan.